Theory and Algorithms of RAIM Augmentation for GNSS - SAKAI, Takeyasu (Electronic Navigation Research Institute papers, 2022)
The satellite navigation system for civil aviation must ensure to provide position information with the required integrity as well as position accuracy. The ICAO (International Civil Aviation Organization) defines GNSS (global navigation satellite system) as the satellite navigation system eligible to be used for civil aviation, which means GPS and GLONASS, operated by the US and Russia, respectively, with the appropriate augmentation necessary to achieve required performance in terms of integrity. Currently SBAS (satellite-based augmentation system), GBAS (ground-based augmentation system), and ABAS (airborne-based augmentation system) are defined as the augmentation system.For SBAS and GBAS, it is possible to evaluate the performance of GNSS over the service area based on a geometry of GPS (or GLONASS) satellites and augmentation information because the international standards specify both the contents and usage of augmentation information. On the other hand, for ABAS, the international standards specify neither particular algorithm nor parameter set. This paper aims to describe theory and algorithms of ABAS, so that it is possible to evaluate the performance of GNSS with ABAS anywhere and anytime. The author reports an investigation of the baseline RAIM (receiver autonomous integrity monitoring) algorithm implemented almost commonly for certified airborne GNSS receivers equipped with ABAS function. Some parameter sets are also given and evaluated in terms of performance and the examples of response to anomalous events of GPS satellite are shown.